2011
DOI: 10.1007/978-94-007-2063-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Modelling Rapid Dynamic Changes of Tidewater Outlet Glaciers: Issues and Implications

Abstract: Recent dramatic acceleration, thinning and retreat of tidewater outlet glaciers in Greenland raises concern regarding their contribution to future sea-level rise. These dynamic changes seem to be parallel to oceanic and climatic warming but the linking mechanisms and forcings are poorly understood and, furthermore, large-scale ice sheet models are currently unable to realistically simulate such changes which provides a major limitation in our ability to predict dynamic mass losses. In this paper we apply a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 107 publications
(69 reference statements)
4
67
0
Order By: Relevance
“…Various numerical models have been used to simulate current submarine melt rates (Jenkins, 2011;Rignot et al, 2016;Sciascia et al, 2013;Xu et al, 2012Xu et al, , 2013 and dynamic retreat Vieli and Nick, 2011) of the GrIS marine-terminating glaciers, as well as ice-dynamic future projections of the whole GrIS (Fürst et al, 2015;Nowicki et al, 2013), due to changes in the oceanic temperatures. However, how this thermal forcing affected the past GrIS configuration has not been explored from a modelling perspective so far.…”
Section: Introductionmentioning
confidence: 99%
“…Various numerical models have been used to simulate current submarine melt rates (Jenkins, 2011;Rignot et al, 2016;Sciascia et al, 2013;Xu et al, 2012Xu et al, , 2013 and dynamic retreat Vieli and Nick, 2011) of the GrIS marine-terminating glaciers, as well as ice-dynamic future projections of the whole GrIS (Fürst et al, 2015;Nowicki et al, 2013), due to changes in the oceanic temperatures. However, how this thermal forcing affected the past GrIS configuration has not been explored from a modelling perspective so far.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have shown that the thinning and acceleration take place in all sections along the flowline, although the emerging consensus view is that they are mainly initiated at the glacier front (Howat and others, 2007;Holland and others, 2008;Nick and others, 2009;Murray and others, 2010). Various forcing mechanisms have been proposed, but large uncertainties remain in their relative importance (Vieli and Nick, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The other half of the mass loss comes from changes in ice discharge -glaciers that drain the ice sheet have accelerated and retreated -but this dynamic component of mass loss is more complicated and poorly understood. The synchronous acceleration of many outlet glaciers originated at their marine termini (Nick et al, 2009;Vieli and Nick, 2011;Howat et al, 2007) and coincided with warming ocean temperatures around Greenland (Holland et al, 2008a; the only time over the past century when glaciers in southeast and west Greenland retreated as much as in the present day was in the 1930s, consistent with the North Atlantic warming. These include the reconstruction of frontal positions of glaciers in southeast and North Atlantic during a negative N has been used to explain the synch ocean heat content anomalies of th the 1950s to 2000s 67,68,32 (Fig.…”
Section: Ocean-glacier Interactions In Greenlandmentioning
confidence: 76%
“…Ocean warming has been implicated as a driver of glacier acceleration and retreat, with enhanced submarine melting as the presumed connection (Holland et al, 2008a;Murray et al, 2010;Vieli and Nick, 2011;Straneo and Heimbach, 2013). In Greenland, however, we have no direct measurements of this melting and only limited understanding of the circulation in fjords where glaciers meet the ocean.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation